The Silent Tarekat in Islamic Law: Legal Consciousness and the Chishti Sufi Legacy of the Tablighi Jamaat - Anshori, Ahmad Yani; Abdurrahman, Landy Trisna; Tamtowi, Moh.; Musaffa, Muhamad Ulul Albab (AHKAM : Jurnal Ilmu Syariah, 2025)
This article explores the silent legal and spiritual framework of the Tablighi Jamaat (TJ) in Indonesia, drawing on fieldwork, interviews, and textual analysis. While TJ does not claim to be a Sufi order (ṭarīqah), its practices suggest a reconfiguration of the Chishti-Ḥanafī legacy within a non-institutional framework. The study argues that TJ operates as a "silent tarekat", where fiqh is embodied through routines of taʿlīm, khurūj, and adab, rather than articulated through fatwā or formal legal discourse. The article traces how collective reasoning (mushāwarah), ethical discipline, and ritual repetition form an alternative legal consciousness that resists codification but remains deeply normative. Drawing from Talal Asad's theory of discursive tradition and Ibn' Arabi's notion of 'ilm al-aḥwāl, the paper shows how authority, legality, and spirituality are distributed through embodied discipline rather than textual claims. Contrasting with mainstream Islamic institutions in Indonesia like NU, Muhammadiyah, and MUI, which rely on fatwā issuance and formal jurisprudence, TJ emphasizes humility, action, and affective cohesion. The article concludes that TJ represents a post-ṭarīqah legal formation, silent, affective, and decentralized, redefining Islamic normativity through practice rather than proclamation.   Abstrak Artikel ini menelusuri kerangka hukum dan spiritual Jamaah Tabligh (JT) di Indonesia yang bersifat diam-diam namun terstruktur, berdasarkan observasi lapangan, wawancara, dan kajian teks. Meskipun Jamaah Tabligh tidak mengklaim diri sebagai tarekat, namun praktiknya menunjukkan konfigurasi ulang warisan Chishti-Ḥanafī dalam bentuk non-institusional. Artikel membawa argumentasi bahwa JT berfungsi sebagai “silent tarekat,” yang mana hukum Islam (fiqh) diwujudkan melalui rutinitas ta’līm, khurūj, dan adab, bukan melalui fatwa atau diskursus hukum formal. Artikel ini mencoba melacak bagaimana musawarah, disiplin etis, dan pengulangan ritual membentuk kesadaran hukum alternatif yang tidak tersusun secara kodifikasi, namun tetap normatif. Mengacu pada teori tradisi diskursif Talal Asad dan konsep ‘ilm al-aḥwāl dari Ibn ʿArabi, tulisan ini menunjukkan bahwa otoritas, legalitas, dan spiritualitas dalam JT tersebar melalui disiplin tubuh, bukan klaim tekstual. Berbeda dengan arus utama lembaga Islam di Indonesia seperti NU, Muhammadiyah, dan MUI yang bergantung pada fatwa dan fikih formal, Jamaah Tabligh menekankan kerendahan hati, amal, dan kohesi afektif. Artikel ini menyimpulkan bahwa Jamaah Tabligh merepresentasikan formasi hukum pasca-tarekat—diam, afektif, dan terdesentralisasi—yang menata ulang normativitas Islam melalui praktik, bukan pernyataan.